Fixed Airflow Obstruction in Asthma: A Problem of the Whole Lung Not of Just the Airways - Rutting, Sandra; Thamrin, Cindy; Cross, Troy J.; King, Gregory G.; Tonga, Katrina O. (Frontiers in Physiology, 2022)
Asthma with irreversible or fixed airflow obstruction (FAO) is a severe clinical phenotype that is difficult to treat and is associated with an accelerated decline in lung function and excess morbidity. There are no current treatments to reverse or prevent this excessive decline in lung function in these patients, due to a lack of understanding of the underlying pathophysiology. The current paradigm is that FAO in asthma is due to airway remodeling driven by chronic inflammation. However, emerging evidence indicates significant and critical structural and functional changes to the lung parenchyma and its lung elastic properties in asthma with FAO, suggesting that FAO is a ‘whole lung’ problem and not just of the airways. In this Perspective we draw upon what is known thus far on the pathophysiological mechanisms contributing to FAO in asthma, and focus on recent advances and future directions. We propose the view that structural and functional changes in parenchymal tissue, are just as (if not more) important than airway remodeling in causing persistent lung function decline in asthma. We believe this paradigm of FAO should be considered when developing novel treatments.